Klasifikasi Pengidap Kanker Payudara Menggunakan Metode Voting Based Extreme Learning Machine (V-ELM) - Dheby Tata Artha; Sigit Adinugroho; Putra Pandu Adikara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Breast cancer is a malignant tumor that formed by the abnormal growth of breast cells. Every year, breast cancer causes about 2,1 million women to die. To reduce the number of deaths caused by breast cancer, screening can be chosen for prevention efforts. The development of medical technology and information technology, in the medical world, can be used by researchers in their fields to develop early detection models, from routine consultation data and blood analysis. In this study, breast cancer data will be classified using the Voting Based Extreme Learning Machine (V-ELM). This study using Coimbra Dataset Breast Cancer which published on UCI Machine Learning in 2018. It consists of 116 data, 9 features and 2 classes (Healthy Control and Patient). Firstly, the dataset would be normalized, then began the training process of V-ELM with data train. After that, began the testing process of V-ELM with input values from the training process and data test. The ratio between training data and testing data in this study is 80:20. This study tested several parameters and obtained optimal results, including 20 hidden neurons, the value of k for V-ELM is 35 and the activation function with optimal results is the Sigmoid function. By using those optimal parameters, gives accuracy of 89.56%, sensitivity of 96.924% and specificity of 80%.